2023
DOI: 10.1186/s12909-023-04842-9
|View full text |Cite
|
Sign up to set email alerts
|

“Tell me what is ‘better’!” How medical students experience feedback, through the lens of self-regulatory learning

Muirne Spooner,
James Larkin,
Siaw Cheok Liew
et al.

Abstract: Introduction While feedback aims to support learning, students frequently struggle to use it. In studying feedback responses there is a gap in explaining them in relation to learning theory. This study explores how feedback experiences influence medical students’ self-regulation of learning. Methods Final-year medical students across three campuses (Ireland, Bahrain and Malaysia) were invited to share experiences of feedback in individual semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Students reported that they needed more guidance and support to overcome these barriers; they preferred clear and explicit instructions and tools on how to read and handle the feedback. This struggle with appropriate learning strategies and the desire for explicit instructions is also reported in earlier studies 17,37–39 . Guidance or explicit suggestions on how to address knowledge gaps could enable students to construct appropriate strategies for improvement 19 …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Students reported that they needed more guidance and support to overcome these barriers; they preferred clear and explicit instructions and tools on how to read and handle the feedback. This struggle with appropriate learning strategies and the desire for explicit instructions is also reported in earlier studies 17,37–39 . Guidance or explicit suggestions on how to address knowledge gaps could enable students to construct appropriate strategies for improvement 19 …”
Section: Discussionmentioning
confidence: 64%
“…This struggle with appropriate learning strategies and the desire for explicit instructions is also reported in earlier studies. 17,[37][38][39] Guidance or explicit suggestions on how to address knowledge gaps could enable students to construct appropriate strategies for improvement. 19 Most students were not willing to act upon the feedback (volition), 17 primarily due to its perceived insignificance and lack of interest.…”
Section: Discussionmentioning
confidence: 99%